(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
As a visual symbol of information, brand identity influences consumers’ perception of brand image and their purchase intention. However, few literatures have examined the influence of brand identity color on consumers’ purchase intention. The present study takes the green brand logo of clothing as a stimulus material to explore the green symbol of its color and the influence of consumers’ green consumption intention. The results show that (1) the color of clothing brand logo has a significant impact on consumers’ green consumption intention. Consumers have the strongest purchase intention aroused by green clothing brand logos, and the weakest purchase intention aroused by red and purple clothing brand logos. (2) Consumers have the strongest purchase intention provoked by dark-colored clothing brand logos, and the weakest purchase intention provoked by light-colored clothing brand logos; (3) Green purchase intention is highly correlated with the symbol of clothing brand logo color.